Language Style in the Novel a Big Plan to Die Quietly Works of Vishnu Suryaning Adji Stillistic Study - Hutagalung, Renaldi; Ritonga, Parlaungan; Harahap, Nurhayati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
One of the ways authors express literary works is through the use of language styles. Language style has a function that can influence the reader which can make the reader interested in what the author conveys. This research is entitled